Integrating soft and hard risks. (24th July 2007) - Blockley, David; Godfrey, Patrick
All organisations need continually to improve and make efficiency savings without introducing unacceptable risks. Savings can be made by new collaborations and sharing at the interface between processes. Processes are what people do and so we use them to deliver value. We can also think and use process differently to improve performance. To identify added value we use a process map which shows how processes relate to each other to integrate various data such as risk registers, KPIs, people and even departments. To do this we use processes as a central spine or skeletal structure to which we associate all data and attributes. This way we expect to align to purpose, unify and simplify, to reduce waste and enhance learning. The role of new process maps and the Italian flag of evidence in adding value are briefly presented.